Characteristics Of Islamic Education In The Qur'an: Analysis Of The Tafsir Of Surat At Tarhim Verse 6 And The Hadith On Family Protection - Mufaizah (Global Action and Education for Society, 2026)
This study examines the interpretation of Surah At-Tahrim verse 6 and selected hadiths related to family protection as the foundation of preventive family-based Islamic education. The study aims to conceptualize Islamic education as a comprehensive protective system encompassing spiritual, moral, and social dimensions, as well as to analyze the role of parents in strengthening family resilience based on Qur’anic and Prophetic guidance. Employing a qualitative approach, this research utilizes thematic interpretation (tafsir maudhu‘i) and hadith content analysis, drawing on classical exegetical works such as those of Ibn Kathir and Ath-Thabari alongside contemporary scholarly literature. The findings indicate that QS. At-Tahrim: 6 emphasizes collective family responsibility in safeguarding members from moral and spiritual deviation through faith cultivation, exemplary conduct, and continuous educational supervision. Relevant hadiths on family protection, including HR. Abu Dawud No. 494, reinforce this mandate by highlighting early religious habituation and an affection-based preventive educational approach. The novelty of this study lies in its integrative framework that combines thematic Qur’anic exegesis with the concept of preventive family education, offering a holistic model of proactive Islamic education oriented toward safeguarding families from both worldly and ukhrawi threats. The study concludes that Qur’anic and Prophetic values should be systematically embedded within a proactive family-based Islamic education system to ensure comprehensive protection and well-being.